Begegnung am Abend Roman - Morton, Brian (Goldmann, 1999)
A failed old writer is visited by a pretty young student who wants to make him the subject of her thesis. The woman's adulation--she tells him his books changed her life--goes to the writer's head and he falls in love. Observing this with a jaundiced eye is his daughter, herself a struggling writer.
Keywords: Authors -- Fiction; Dissertations, Academic -- Fiction; Verlieben; Alter; Schriftsteller; Studentin; Fiktionale Darstellung; Psychological fiction